A novel light-dependent activation of DAGK and PKC in bovine photoreceptor nuclei - Natalini, Paola Marisel (2014)
In this work, we describe a selective light-dependent distribution of the lipid kinase 1,2-diacylglycerol kinase (EC 2.7.1.107, DAGK) and the phosphorylated protein kinase C alpha (pPKCalpha) in a nuclear fraction of photoreceptor cells from bovine retinas. A nuclear fraction enriched in small nuclei from photoreceptor cells (PNF), was obtained when a modified nuclear isolation protocol developed by our laboratory was used. We measured and compared DAGK activity as phosphatidic acid (PA) formation in PNF obtained from retinas exposed to light and in retinas kept in darkness using [gamma-32P]ATP or [3H]DAG. In the absence of exogenous substrates and detergents, no changes in DAGK activity were observed. However, when DAGK activity assays were performed in the presence of exogenous substrates, such as stearoyl arachidonoyl glycerol (SAG) or dioleoyl glycerol (DOG), and different detergents (used to make different DAGK isoforms evident), we observed significant light effects on DAGK activity, suggesting the presence of several DAGK isoforms in PNF. Under conditions favoring DAGKzeta activity (DOG, Triton X-100, dioleoyl phosphatidylserine and R59022) we observed an increase in PA formation in PNF from retinas exposed to light with respect to those exposed to darkness. In contrast, under conditions favoring DAGKepsilon (SAG, octylglucoside and R59022) we observed a decrease in its activity. These results suggest different physiological roles of the above-mentioned DAGK isoforms. Western blot analysis showed that whereas light stimulation of bovine retinas increases DAGKzeta nuclear content, it decreases DAGKepsilon and DAGKbeta content in PNF. The role of PIP2-phospholipase C in light-stimulated DAGK activity was demonstrated using U73122. Light was also observed to induce enhanced pPKCalpha content in PNF. The selective distribution of DAGKzeta and epsilon in PNF could be a light-dependent mechanism that in vertebrate retina promotes selective DAG removal and PKC regulation.